How Good at Neurology are you? – Answers. Issue 6 (1st December 2004) - Goldsmith, Paul; Lennox, Graham; Ray, Julian
Abstract : 1. Skull base meningioma The images show a large lobulated mass growing from the skull base, with moderate homogenous enhancement. These features are typical of a meningioma. Note the very prominent musculature surrounding the skull. These images are from a dog! Sites of skull base meningiomas include the sphenoid bone, optic sheath, olfactory groove, planum tuberculum and petrous bone. They are divided into en plaque forms, which are flatter and grow along the dura, and en masse forms which bulge inwards and often have a dural tail visible post contrast. 2. F F F T F Susac's syndrome is the triad of encephalopathy, sensori-neural hearing loss and retinal branch artery occlusions. The encephalopathy, if severe, can make the detection of the visual and auditory deficits difficult. The underlying pathology is a non-inflammatory microangiopathy resulting in small infarcts in the cochlea, retina and brain. The typical